Governance issues in developing and implementing offsets for water management benefits: Can preliminary evaluation guide implementation effectiveness?. (16th January 2015) - Feldman, David L.; Sengupta, Ashmita; Stuvick, Lindsey; Stein, Eric; Pettigrove, Vin; Arora, Meenakshi
Abstract : This article explores governance issues in developing innovative pollutant offset programs by focusing on a case study being piloted at the Gisborne Recycled Water Plant in Jackson Creek, a rural subcatchment of the Maribyrnong River north of Melbourne, Australia. The article offers preliminary lessons from the ongoing design and anticipated challenges facing this innovative program based on reflections from the literature and project progress to‐date. This case exemplifies a form of adaptive governance—an approach well suited to achieving broad sustainability objectives—and for which an early assessment is both appropriate and opportune. Adaptive governance is characterized by governmental collaboration with civil society groups, social learning through public participation, and experimentation leading to more flexible policy outcomes. Early assessment affords the possibility of midcourse corrections, drawing on experience acquired elsewhere. We contend that the approach being developed in Victoria through this pilot program has implications beyond the use of recycled wastewater for achieving various social objectives. It may also contribute to the development of an expansive water quality offset framework applicable to point source discharges, nonpoint source pollution, and sewerage overspills. Moreover, the approach can be applied to design of offset systems elsewhere—with appropriate economic savings and effective application to multiple water quality challenges if potential problems are discerned early. WIREs Water 2015, 2:121–130. doi: 10.1002/wat2.1061 This article is categorized under: Engineering Water > Planning Water Engineering Water > Sustainable Engineering of Water Engineering Water > Water, Health, and Sanitation